Supplemental ultraviolet-B radiation does not reduce growth or grain yield in rice - Dai, Qiujie; Peng, Shaobing; Chavez, Arlene Q.; Miranda, Ma. Lourdes L.; Vergara, Benito S.; Olszyk, David M. (Wiley, 1997)
Negative effects of enhanced UV‐B radiation have been demonstrated in plants, but impacts under realistic field conditions remain uncertain. Adverse impacts to major crops, such as rice (Oryza sativa L.), that are grown in areas with currently high ambient levels of UV‐B, could have consequences for food security. To address the response of rice to UV‐B, we conducted an intensive and extensive series of field experiments from 1992 to 1995 documenting the effects of supplemental UV‐B (simulating approximately 20% ozone depletion for the Philippines), using irrigated rice cultivars under tropical conditions. This multiseason study indicated that supplemental UV‐B had no significant effects on rice grain yield (including the yield components spikelet filling percentage, and 1000‐grain weight) or growth parameters (plant height or panicles per square meter). The absence of UV‐B effects was consistent across seasonal environment (four dry and three wet seasons), cultivar, and type of exposure system. Thus, rice yields are not likely to be affected by increases in UV‐B under realistic field conditions.